PENGARUH LOKASI, SPESIFIKASI BANGUNAN DAN PROMOSI TERHADAP MINAT BELI KONSUMEN PERUMAHAN GOVINDA HILL RESIDENCE II PADA PT ARTHA MITRA GOVINDA DI BATURAJA - Made Kompyang; Rini Apriyani (KOLEGIAL, 2021)
The purpose of this study was to determine the effect of location, building specifications and promotions on consumer buying interest in Govinda Hill Residence II Housing at PT Artha Mitra Govinda in Baturaja. The research method used in this research is descriptive method. Based on the results of the research and discussion conducted, Correlation value (R) 0.769. This value shows that the correlation between all location variables (X1), building specifications (X2), promotion (X3) and consumer buying interest (Y) Govinda Hill Residence II Housing at PT Artha Mitra Govinda in Baturaja is very strong because it is at the interval 0 .75 – 0.99 (Sarwono, 2006:107). The value of the coefficient of determination (R Square) is equal to 0.592 or 59.2%. Based on the t-test, the building specification variable (X2) and the promotion variable (X3) partially have an effect on consumer buying interest in Govinda Hill Residence II Housing at PT Artha Mitra Govinda in Baturaja. Based on the F test, the Fcount value is 14,507. While the Ftable value of 2.92 obtained from df = n-k-1 (df = 34-3-1) with a significant level of 5% and a 95% confidence level. With the value of Fcount greater than the value of Ftable, namely (14,507 > 2,92), the conclusion is Ho is rejected and Ha is accepted. This means that together there is an effect of location variables (X1), building specifications (X2), promotions (X3) on consumer buying interest (Y) Govinda Hill Residence II Housing at PT Artha Mitra Govinda in Baturaja.